Free Theatre : the 37 year experiment - Horrocks, Shirley; Point of View Productions (Auckland, N.Z.) ([Auckland, New Zealand] : Point of View Productions, 2017)
The inside story of Free Theatre: the colourful and controversial theatre company in Christchurch, New Zealand, which has been creating extraordinary productions for 37 years. The group has specialised in physical theatre, innovative forms of European drama, and collaborations with music and the visual arts. Since the Christchurch earthquakes it has developed new styles of performance to involve the community and interact with the city's devastated landscapes.
Title from title screen (viewed July 19, 2021).
Narration, Jennifer Ward-Lealand.
In English.
Keywords: Theater -- New Zealand -- Christchurch; Theaters -- New Zealand -- Christchurch; Theater and society -- New Zealand -- Christchurch; Théâtre -- Nouvelle-Zélande -- Christchurch; Théâtre et société -- Nouvelle-Zélande -- Christchurch; Theater; Theater and society; Theaters; New Zealand -- Christchurch; Documentaries and Factual Films; Documentary films; Documentary films; Documentaires